Method for recycling of polishing powder secondary waste in the preparation of magnesium-aluminum-carbon bricks

CN123003262APending Publication Date: 2026-10-30INNER MONGOLIA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611495177.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]抛光粉二次废料的回收不仅难度较高,处理成本也居高不下,大部分废料在使用结束后都会被直接丢弃,成为难以处置的固体废弃物

Benefits of technology

本发明在固化阶段,采用三段式升温方式,一方面避免升温过快造成砖体产生微裂纹,对砖体强度与致密性造成负面影响,另一方面在此三段式升温方式下,可以使得砖体内部的水分有序排出,避免因砖体内部水分对砖体造成影响。同时此三段式升温方式可以使得酚醛树脂分解产生的二氧化碳与水有序排列,使得其形成微小的气孔通道,进一步加强其与外部环境的沟通,避免大气孔通道的形成,进一步提高砖体的致密性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003262A_ABST
    Figure CN123003262A_ABST
Patent Text Reader

Abstract

This invention relates to a method for recycling secondary waste polishing powder in the preparation of magnesia-alumina-carbon bricks. The method comprises: first, adding magnesium oxide particles of different sizes into a planetary mixer, then adding phenolic resin, white corundum powder, carbon powder, and secondary waste polishing powder, and mixing thoroughly to obtain a slurry; pressing the slurry into shape using a fully automatic constant pressure testing machine; and finally, placing the brick blank in an electric furnace for curing using a three-stage heating method, followed by heat preservation and cooling to obtain magnesia-alumina-carbon bricks. This invention employs a three-stage heating method, which effectively avoids excessively rapid heating that could cause micro-cracks in the brick body, thus improving the brick's strength and density. The CeO2 on the brick surface and inside undergoes Ce2 oxidation at high temperatures. 4+ With Ce 3+ Interconversion occurs, creating a certain amount of oxygen vacancies. Rare earth element Ce 3+ It reacts with Al to form CeAlO3, which improves the brick's resistance to steel slag corrosion. Oxygen vacancies on the brick surface are more likely to form an oxide film, thus extending the brick's service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of magnesium-aluminate-carbon bricks, specifically relating to a method for recycling secondary waste polishing powder in the preparation of magnesium-aluminate-carbon bricks. Background Technology

[0002] Magnesia-alumina-carbon bricks are widely used in the steel metallurgy field, particularly in converters and ladle slag areas, due to their unique properties. Converters, in particular, have higher requirements for the erosion resistance of magnesia-alumina-carbon bricks, and high-carbon, high-density magnesia-alumina-carbon bricks are generally selected in production.

[0003] The recycling of secondary waste from polishing powder is not only difficult but also costly. Most of this waste is simply discarded after use, becoming difficult-to-dispose-of solid waste. The existence of this waste not only pollutes the environment but also leads to the needless waste of my country's rare earth cerium resources.

[0004] However, the secondary waste from polishing powder is rich in rare earth components such as cerium oxide, which exhibit good chemical stability and high hardness, and demonstrates excellent resistance to erosion and oxidation under high-temperature environments. This aligns well with the performance requirements of magnesia-alumina-carbon bricks. Therefore, if the secondary waste from polishing powder can be introduced into the preparation system of magnesia-alumina-carbon bricks as a functional additive or partial substitute, it can not only alleviate the environmental pressure caused by its disposal but also achieve the cascade utilization of rare earth resources, improving the overall service performance of magnesia-alumina-carbon bricks, thus possessing significant economic value and environmental significance. Summary of the Invention

[0005] The purpose of this invention is to provide a method for recycling secondary waste polishing powder in the preparation of magnesium aluminate carbon bricks, aiming to achieve efficient resource utilization of secondary waste polishing powder, improve the density of magnesium aluminate carbon bricks, and enhance their service life.

[0006] The technical solution adopted by this invention to solve the technical problem is as follows: The present invention provides a method for recycling secondary waste polishing powder in the preparation of magnesium aluminate carbon bricks, which mainly includes the following steps: Step S1: First, put magnesium oxide particles of different sizes into a planetary mixer for mixing, then add phenolic resin, white corundum powder, carbon powder and polishing powder secondary waste, mix evenly to obtain well coated mud. Step S2: Press the mixed mud into shape using a fully automatic constant pressure testing machine; Step S3: Place the pressed brick blank into an electric furnace and cure it using a three-stage heating method. After heat preservation and cooling, magnesia-alumina-carbon bricks are obtained.

[0007] In a preferred embodiment, the particle sizes of the magnesium oxide particles are 0-1 mm, 1-3 mm, and 3-5 mm, respectively.

[0008] In a preferred embodiment, the mass ratio of magnesium oxide particles with particle sizes of 0-1 mm, 1-3 mm and 3-5 mm is (21.5-22.5):(27-28):(25-26).

[0009] In a preferred embodiment, the mass ratio of the magnesium oxide particles, phenolic resin, white corundum powder, carbon powder and polishing powder secondary waste is (84-85.5):(3-4):(2-3):(10-11):(1-3).

[0010] In a preferred embodiment, in step S2, the molding pressure of the fully automatic constant pressure testing machine is 150-300MPa, and the holding time is 3-5s.

[0011] In a preferred embodiment, the three-stage heating method in step S3 is as follows: In the first stage, the temperature is increased from 20℃ to 100℃ at a heating rate of 3-4℃ / min, and held for 1.5-2.5 hours. In the second stage, the temperature is increased from 100℃ to 150℃ at a heating rate of 4-5℃ / min, and held for 2.5-3.5 hours. In the third stage, the temperature is increased from 150℃ to 200℃ at a heating rate of 5-6℃ / min, and held for 7.5-8.5 hours.

[0012] In a preferred embodiment, the secondary waste polishing powder contains Al2O3, CaO, Fe2O3, MgO, SiO2 and REO.

[0013] The present invention provides a method for preparing magnesium-alumina-carbon bricks by recycling the secondary waste of polishing powder in the preparation of magnesium-alumina-carbon bricks.

[0014] In a preferred embodiment, the magnesium-aluminum-carbon brick comprises: magnesium oxide particles, phenolic resin, white corundum powder, carbon powder, and polishing powder secondary waste; the mass ratio of the magnesium oxide particles, phenolic resin, white corundum powder, carbon powder, and polishing powder secondary waste is (84-85.5):(3-4):(2-3):(10-11):(1-3).

[0015] The beneficial effects of this invention are: In the curing stage, this invention employs a three-stage heating method. This method avoids excessively rapid heating that could cause micro-cracks in the brick, negatively impacting its strength and density. Furthermore, this three-stage heating method allows for the orderly drainage of internal moisture, preventing it from affecting the brick's structure. Simultaneously, this three-stage heating method enables the carbon dioxide and water produced by the decomposition of phenolic resin to arrange themselves in an orderly manner, forming tiny pore channels. This further enhances the brick's communication with the external environment, preventing the formation of large pore channels and further improving its density.

[0016] During use, CeO2 on the surface and inside the magnesium aluminate carbon brick reacts with CeO2 at high temperatures. 4+ Ce 3+ The interconversion behavior creates a certain amount of oxygen vacancies; these oxygen vacancies more easily form an oxide film on the surface of magnesia-alumina-carbon bricks, further inhibiting the erosion of the bricks by steel slag and extending the service life of the magnesia-alumina-carbon bricks. Simultaneously, the rare earth element Ce inside the magnesia-alumina-carbon bricks... 3+ It also reacts with Al to form CeAlO3, further enhancing the erosion resistance of magnesia-alumina-carbon bricks. In addition, the secondary waste from polishing powder also contains a certain amount of La. 3+ Under high temperature conditions, it reacts with Al to form LaAlO3, which can also improve the corrosion resistance of magnesium aluminate carbon bricks and thus extend their service life. Attached Figure Description

[0017] Figure 1 The four magnesium-aluminate-carbon bricks obtained in Example 1 are shown.

[0018] Figure 2 The microstructure (surface) of the four magnesium-aluminate-carbon bricks obtained in Example 2 is shown in the figure. In the figure, (a) is 150 MPa, (b) is 200 MPa, (c) is 250 MPa, and (d) is 300 MPa.

[0019] Figure 3 The image shows the microstructure (cross-section) of four magnesium aluminate carbon bricks obtained in Example 2. In the figure, (a) represents 150 MPa, (b) represents 200 MPa, (c) represents 250 MPa, and (d) represents 300 MPa.

[0020] Figure 4 The images show the SEM images of the experimental group (3#) and the blank control group (6#) after slag erosion resistance in Example 3.

[0021] Figure 5 The image shows the XRD pattern of experimental group (3#) in Example 3. Detailed Implementation

[0022] In a first aspect, the present invention provides a method for recycling secondary waste polishing powder in the preparation of magnesium aluminum carbon bricks.

[0023] The present invention provides a method for recycling secondary waste polishing powder in the preparation of magnesium aluminate carbon bricks, the specific implementation process of which is as follows: Step S1: First, put three types of magnesium oxide particles with particle sizes of 0-1mm, 1-3mm and 3-5mm into a planetary mixer and stir them in a mass ratio of (21.5-22.5):(27-28):(25-26). Then, add phenolic resin, white corundum powder, carbon powder and polishing powder secondary waste in a mass ratio of (84-85.5):(3-4):(2-3):(10-11):(1-3) respectively, stir evenly, and obtain a well coated mud. The secondary waste from polishing powder contains Al2O3, CaO, Fe2O3, MgO, SiO2, and REO.

[0024] The preferred particle size of the white fused alumina powder is 320 mesh, and its α-Al2O3 content is greater than 99%.

[0025] The preferred particle size of the toner is 100 mesh.

[0026] Step S2: Press the mixed mud into shape using a fully automatic constant pressure testing machine. The molding pressure is 150-300MPa, and the holding time is 3-5s.

[0027] Step S3: Place the pressed brick blank into an electric furnace and cure it using a three-stage heating method. After heat preservation and cooling, magnesia-alumina-carbon bricks are obtained.

[0028] The preferred three-stage heating method is: The temperature was increased from 20℃ to 200℃ at a heating rate of 3-6℃ / min.

[0029] Among them, the three-stage heating method is more preferably: In the first stage, the temperature is increased from 20℃ to 100℃ at a heating rate of 3-4℃ / min, and held for 1.5-2.5 hours. In the second stage, the temperature is increased from 100℃ to 150℃ at a heating rate of 4-5℃ / min, and held for 2.5-3.5 hours. In the third stage, the temperature is increased from 150℃ to 200℃ at a heating rate of 5-6℃ / min, and held for 7.5-8.5 hours.

[0030] Secondly, the present invention provides a method for recycling secondary waste polishing powder provided in the first aspect in the preparation of magnesium aluminate carbon bricks to obtain magnesium aluminate carbon bricks.

[0031] Magnesium aluminum carbon bricks mainly consist of: magnesium oxide particles, phenolic resin, white corundum powder, carbon powder, and secondary waste from polishing powder.

[0032] The preferred mass ratio of magnesium oxide particles, phenolic resin, white corundum powder, carbon powder and polishing powder secondary waste is (84-85.5):(3-4):(2-3):(10-11):(1-3).

[0033] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0034] Example 1: Determination of the optimal polishing powder for secondary waste This embodiment provides a method for recycling secondary waste polishing powder in the preparation of magnesium-aluminum-carbon bricks. The specific operation steps are as follows: Step S1: First, put three types of magnesium oxide particles with particle sizes of 0-1mm, 1-3mm, and 3-5mm into a planetary mixer and stir for 3 minutes at a mass ratio of 22:28:26. Then, add phenolic resin, white corundum powder, carbon powder, and secondary waste polishing powder (1#, 2#, 3#) to the mixture at a mass ratio of 85.5:3:2:11:2 and stir evenly to obtain a well-coated mud. At the same time, a blank control group (4#) without secondary waste polishing powder is set up. The composition of the secondary waste polishing powder (1#, 2#, 3#) is shown in Table 1.

[0035] Table 1. Composition of Secondary Waste from Polishing Powder

[0036] Step S2: Press the mixed mud into shape using a fully automatic constant pressure testing machine. The molding pressure is 150MPa and the holding time is 5s. Step S3: Place the pressed brick blank into an electric furnace and cure it using a three-stage heating method. After heat preservation and cooling, magnesia-alumina-carbon bricks are obtained.

[0037] The three-stage heating method is as follows: In the first stage, the temperature was increased from 20℃ to 100℃ at a heating rate of 3℃ / min and held for 2 hours. In the second stage, the temperature was increased from 100℃ to 150℃ at a heating rate of 4℃ / min and held for 3 hours. In the third stage, the temperature was increased from 150℃ to 200℃ at a heating rate of 5℃ / min, and held for 8 hours.

[0038] The four magnesium-aluminate-carbon bricks (1#, 2#, 3#, and 4#) obtained in this embodiment were cut sequentially, and the results are as follows. Figure 1 As shown, brick samples 1#, 2#, and 3# were prepared by incorporating secondary waste polishing powder 1#, 2#, and 3#, respectively, while sample 4# was the blank control group. The test results showed that the magnesia-alumina-carbon brick prepared with secondary waste polishing powder 2# exhibited the best performance, with only a few minor cracks on the brick surface, causing no damage to the brick body. In contrast, the magnesia-alumina-carbon bricks prepared with secondary waste polishing powder 1# and 3# showed severe damage. Therefore, secondary waste polishing powder 2# was selected as the optimal secondary waste polishing powder.

[0039] Example 2: Determination of Optimal Molding Pressure This embodiment provides a method for recycling secondary waste polishing powder in the preparation of magnesium-aluminum-carbon bricks. The specific operation steps are as follows: Step S1: First, put three types of magnesium oxide particles with particle sizes of 0-1mm, 1-3mm and 3-5mm into a planetary mixer and stir for 3 minutes in a mass ratio of 22:28:26. Then, add phenolic resin, white fused alumina powder, carbon powder and polishing powder secondary waste (2#) in a mass ratio of 85.5:3:2:11:2 and stir evenly to obtain a well coated mud. Step S2: Press the mixed mud into shape using a fully automatic constant pressure testing machine, setting different molding pressures (150MPa, 200MPa, 250MPa, 300MPa), with a holding time of 5s; Step S3: Place the pressed brick blank into an electric furnace and cure it using a three-stage heating method. After heat preservation and cooling, magnesia-alumina-carbon bricks are obtained.

[0040] The three-stage heating method is as follows: In the first stage, the temperature was increased from 20℃ to 100℃ at a heating rate of 3℃ / min and held for 2 hours. In the second stage, the temperature was increased from 100℃ to 150℃ at a heating rate of 4℃ / min and held for 3 hours. In the third stage, the temperature was increased from 150℃ to 200℃ at a heating rate of 5℃ / min, and held for 8 hours.

[0041] The microstructure of the four magnesium-aluminate-carbon bricks obtained in this embodiment was observed, and the results are as follows: Figure 2 and Figure 3As shown in the results, the test results reveal significant differences in the sample surface and cross-section under different molding pressures. This is because the particle compaction varies under different molding pressures. If the molding pressure is too low, the particles are not compact enough, resulting in a loose sample surface and cross-section; if the molding pressure is too high, the particles are easily crushed, disrupting the particle size distribution, leading to a porous sample surface and cross-section. Based on the microstructure results, 250 MPa was selected as the optimal molding pressure.

[0042] Example 3: Determination of the optimal amount of secondary waste to be added to the polishing powder This embodiment provides a method for recycling secondary waste polishing powder in the preparation of magnesium-aluminum-carbon bricks. The specific operation steps are as follows: Step S1: First, put three types of magnesium oxide particles with particle sizes of 0-1mm, 1-3mm and 3-5mm into a planetary mixer in a mass ratio of 22:28:26 and stir for 3 minutes. Then, add phenolic resin, white fused alumina powder, carbon powder and polishing powder secondary waste (2#) in different mass ratios and stir evenly to obtain a well coated mud. Step S2: Press the mixed mud into shape using a fully automatic constant pressure testing machine. The molding pressure is 250MPa and the holding time is 5s. Step S3: Place the pressed brick blank into an electric furnace and cure it using a three-stage heating method. After heat preservation and cooling, magnesia-alumina-carbon bricks are obtained.

[0043] The three-stage heating method is as follows: In the first stage, the temperature was increased from 20℃ to 100℃ at a heating rate of 3℃ / min and held for 2 hours. In the second stage, the temperature was increased from 100℃ to 150℃ at a heating rate of 4℃ / min and held for 3 hours. In the third stage, the temperature was increased from 150℃ to 200℃ at a heating rate of 5℃ / min, and held for 8 hours.

[0044] The six magnesium-aluminate-carbon bricks obtained in this embodiment were subjected to room temperature performance tests, as detailed below: (1) Test the bulk density and apparent porosity of magnesium aluminate carbon bricks according to GB / T 2997; (2) Test the compressive strength of magnesium aluminate carbon bricks at room temperature according to GB / T 5072.

[0045] (3) Among them, 1#, 2#, 3#, 4#, and 5# represent experimental groups with 1%, 1.5%, 2%, 2.5%, and 3% secondary waste polishing powder added, respectively, and the amounts of magnesium oxide particles, phenolic resin, white corundum powder, and carbon powder added in each experimental group are the same; 6# represents the blank control group without secondary waste polishing powder. The SEM images of the experimental group (3#) and the blank control group (6#) after slag erosion resistance are shown in the figure. Figure 4 As shown.

[0046] Table 2 Results of room temperature performance tests

[0047] Table 2 shows that the amount of secondary waste polishing powder added has a significant impact on the room temperature performance of magnesia-alumina-carbon bricks. When the amount of secondary waste polishing powder added is low, the room temperature performance of the magnesia-alumina-carbon bricks decreases. This is because when a small amount of secondary waste polishing powder is added, it does not change the overall structure of the brick body; rare earth ions cannot disperse and distribute within the brick body, only a small amount accumulates, and most areas of the brick body do not have rare earth ion enrichment, therefore the rare earth ions cannot play their role. Furthermore, from... Figure 5 It can be seen that the rare earth element Ce inside the magnesium-aluminum-carbon brick 3+ It also reacts with Al to form CeAlO3, further improving the erosion resistance of magnesia-alumina-carbon bricks. From the above experimental results, it can be seen that sample number 3 has the best performance; therefore, the amount of secondary waste polishing powder added corresponding to this number is selected as the optimal amount.

[0048] Example 4: Determination of the optimal three-stage heating method This embodiment provides a method for recycling secondary waste polishing powder in the preparation of magnesium-aluminum-carbon bricks. The specific operation steps are as follows: Step S1: First, put three types of magnesium oxide particles with particle sizes of 0-1mm, 1-3mm and 3-5mm into a planetary mixer and stir for 3 minutes in a mass ratio of 22:28:26. Then, add phenolic resin, white fused alumina powder, carbon powder and secondary polishing powder waste (2#) in the optimal mass ratio of 85.5:3:2:11:2 and stir evenly to obtain a well coated mud. Step S2: Press the mixed mud into shape using a fully automatic constant pressure testing machine. The optimal molding pressure is 250MPa and the holding time is 5s. Step S3: Place the pressed brick blanks into an electric furnace and cure them using different three-stage heating methods. After heat preservation and cooling, the optimal magnesium-aluminate-carbon bricks are obtained.

[0049] The first of the three-stage heating method is: In the first stage, the temperature was increased from 20℃ to 50℃ at a heating rate of 3℃ / min, and held for 2 hours. In the second stage, the temperature was increased from 50℃ to 80℃ at a heating rate of 4℃ / min, and held for 3 hours. In the third stage, the temperature was increased from 80℃ to 100℃ at a heating rate of 4℃ / min, and held for 8 hours.

[0050] Three-stage heating method 2 is as follows: In the first stage, the temperature was increased from 20℃ to 80℃ at a heating rate of 3℃ / min, and held for 2 hours. In the second stage, the temperature was increased from 80℃ to 120℃ at a heating rate of 4℃ / min and held for 3 hours. In the third stage, the temperature was increased from 120℃ to 150℃ at a heating rate of 5℃ / min, and held for 8 hours.

[0051] The third of the three-stage heating methods is: In the first stage, the temperature was increased from 20℃ to 100℃ at a heating rate of 3℃ / min and held for 2 hours. In the second stage, the temperature was increased from 100℃ to 150℃ at a heating rate of 4℃ / min and held for 3 hours. In the third stage, the temperature was increased from 150℃ to 200℃ at a heating rate of 5℃ / min, and held for 8 hours.

[0052] The fourth of the three-stage heating methods is: In the first stage, the temperature was increased from 20℃ to 120℃ at a heating rate of 3℃ / min, and held for 2 hours. In the second stage, the temperature was increased from 120℃ to 180℃ at a heating rate of 4℃ / min and held for 3 hours. In the third stage, the temperature was increased from 180℃ to 250℃ at a heating rate of 5℃ / min, and held for 8 hours.

[0053] The room temperature performance of the different magnesium-aluminate-carbon bricks obtained in this embodiment was tested, as follows: (1) Test the bulk density and apparent porosity of magnesium aluminate carbon bricks according to GB / T 2997; (2) Test the compressive strength of magnesium aluminate carbon bricks at room temperature according to GB / T 5072.

[0054] Table 3. Results of room temperature performance tests

[0055] Table 3 shows that the apparent porosity is lower at lower temperatures because the phenolic resin inside the brick is not completely decomposed at low temperatures, leaving a large amount of CO2 and H2O inside the brick. During use, these gases will be released from the brick as the temperature rises, accelerating brick aging and reducing its service life. Samples numbered 3 and 4 show a small difference in apparent porosity, but a significant difference in bulk density and compressive strength. This is because as the temperature increases, the carbon on the brick surface oxidizes with the oxygen in the furnace air, reducing the surface weight of the brick and thus lowering its bulk density. The experimental results show that sample number 3 has the best performance; therefore, the three-stage heating method corresponding to sample number 3 is selected as the optimal three-stage heating method.

[0056] This invention discloses a method for recycling secondary waste polishing powder in the preparation of magnesium-aluminate-carbon bricks. Those skilled in the art can refer to this document and appropriately modify the process parameters to achieve the desired result. It is particularly important to note that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The product of this invention has been described through preferred embodiments, and those skilled in the art can clearly modify or appropriately change and combine the product described herein without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.

Claims

1. A method for recycling secondary waste polishing powder in the preparation of magnesium aluminate carbon bricks, characterized in that, Includes the following steps: Step S1: First, put magnesium oxide particles of different sizes into a planetary mixer for mixing, then add phenolic resin, white corundum powder, carbon powder and polishing powder secondary waste, mix evenly to obtain well coated mud. Step S2: Press the mixed mud into shape using a fully automatic constant pressure testing machine; Step S3: Place the pressed brick blank into an electric furnace and cure it using a three-stage heating method. After heat preservation and cooling, magnesia-alumina-carbon bricks are obtained.

2. The method for recycling secondary waste polishing powder in the preparation of magnesium-aluminum-carbon bricks according to claim 1, characterized in that, The magnesium oxide particles have particle sizes of 0-1 mm, 1-3 mm, and 3-5 mm, respectively.

3. The method for recycling secondary waste polishing powder in the preparation of magnesium-aluminum-carbon bricks according to claim 2, characterized in that, The mass ratio of magnesium oxide particles with particle sizes of 0-1 mm, 1-3 mm and 3-5 mm is (21.5-22.5):(27-28):(25-26).

4. The method for recycling secondary waste polishing powder in the preparation of magnesium-aluminate-carbon bricks according to claim 1, characterized in that, The mass ratio of the secondary waste materials, namely magnesium oxide particles, phenolic resin, white corundum powder, carbon powder and polishing powder, is (84-85.5):(3-4):(2-3):(10-11):(1-3).

5. The method for recycling secondary waste polishing powder in the preparation of magnesium-aluminate-carbon bricks according to claim 1, characterized in that, In step S2, the molding pressure of the fully automatic constant pressure testing machine is 150-300MPa, and the holding time is 3-5s.

6. The method for recycling secondary waste polishing powder in the preparation of magnesium-aluminate-carbon bricks according to claim 1, characterized in that, In step S3, the three-stage heating method is as follows: In the first stage, the temperature is increased from 20℃ to 100℃ at a heating rate of 3-4℃ / min, and held for 1.5-2.5 hours. In the second stage, the temperature is increased from 100℃ to 150℃ at a heating rate of 4-5℃ / min, and held for 2.5-3.5 hours. In the third stage, the temperature is increased from 150℃ to 200℃ at a heating rate of 5-6℃ / min, and held for 7.5-8.5 hours.

7. The method for recycling secondary waste polishing powder in the preparation of magnesium-aluminate-carbon bricks according to claim 1, characterized in that, The polishing powder secondary waste contains Al2O3, CaO, Fe2O3, MgO, SiO2 and REO.

8. Magnesium-alumina carbon bricks prepared by the method of recycling secondary waste polishing powder in the preparation of magnesium-alumina carbon bricks according to any one of claims 1-7.

9. The magnesium-aluminate-carbon brick according to claim 8, characterized in that, The magnesium-aluminum-carbon brick comprises: magnesium oxide particles, phenolic resin, white corundum powder, carbon powder and polishing powder secondary waste; the mass ratio of the magnesium oxide particles, phenolic resin, white corundum powder, carbon powder and polishing powder secondary waste is (84-85.5):(3-4):(2-3):(10-11):(1-3).